Helminth Infections Induce Tissue Tolerance Mitigating Immunopathology but Enhancing Microbial Pathogen Susceptibility - Yap, George S.; Gause, William C. (Frontiers in Immunology, 2018)
Helminths are ubiquitous and have chronically infected vertebrates throughout their evolution. As such helminths have likely exerted considerable selection pressure on our immune systems. The large size of multicellular helminths and their limited replicative capacity in the host necessarily elicits different host protective mechanisms than the immune response evoked by microbial pathogens such as bacteria, viruses and intracellular parasites. The cellular damage resulting from helminth migration through tissues is a major trigger of the type 2 and regulatory immune responses, which activates wound repair mechanisms that increases tissue tolerance to injury and resistance mechanisms that enhance resistance to further colonization with larval stages. While these wound healing and anti-inflammatory responses may be beneficial to the helminth infected host, they may also compromise the host’s ability to mount protective immune responses to microbial pathogens. In this review we will first describe helminth-induced tolerance mechanisms that develop in specific organs including the lung and the intestine, and how adaptive immunity may contribute to these responses through differential activation of T cells in the secondary lymphoid organs. We will then integrate studies that have examined how the immune response is modulated in these specific tissues during coinfection of helminths with viruses, protozoa, and bacteria.